Electronic Word Of Mouth (eWOM) On Social Networking Sites and Its Effect on Brand Reputation Management - Tibrewala, Aditya (2011)
An research into why consumers post brand related content on social networking websites and how it positively/negatively affects a brands reputation on social networking websites. The effect of eWOM on brands and what brands should do to make the best of it and avoid the worst.